LIST OF WITNESSES TO APPEAR BEFORE COMMITTEE ON WAYS AND MEANS ON THE FINANCING PROVISIONS OF THE ADMINISTRATION'S HEALTH SECURITY ACT AND OTHER HEALTH REFORM PROPOSALS (Tufts Archival Research Center, 2007)
List of witnesses who will be testifying before the Ways and Means Committee regarding the financing of the Clinton Administration's Health Security Act as well as other health reform proposals.